Numerical Evaluation of the Direct Method for Cohesive Law Extraction in Shear by the End-Notched Flexure Test - Fernandes, R.L. (2020)
With adhesive bonding, design can be oriented towards lighter structures, not only regarding the direct weight saving advantages of the joint over fastened or welded joints, but also because of flexibility to joint different materials. Cohesive Zone Models (CZM) are a powerful design tool, although the CZM laws of the adhesive bond in tension and shear are required as input in the models. This work evaluated the shear fracture toughness and CZM laws of bonded joints. The End-Notched Flexure (ENF) test geometry was used with this purpose. The experimental work consisted on the shear fracture characterization of the bond by conventional and the J-integral techniques. Additionally, by the J-integral technique, the precise shape of the cohesive law was defined. Numerical Finite Element (FE) simulations were carried out in Abaqus® to assess the accuracy of the obtained CZM laws in predicting the experimental behaviour of the ENF tests, with positive results. As output of this work, fracture data is provided in shear for the selected adhesive, allowing the subsequent strength prediction of bonded joints.